Non-academic support helps international postgraduate researchers succeed in their studies - Gilbert, David J.; Poliah, Keren; Helm, Hannah; Milburn, Maggie; Yates, Katherine (Journal of International Students, 2026)
International postgraduate researchers (PGRs) are students who undertake postgraduate research in a country other than their country of origin. Following the United States (US), the United Kingdom (UK) is the second most common destination for PGRs. When international PGRs travel for educational purposes, they encounter multiple challenges. This article explores the experiences and needs of international PGRs as they settle into academic life in the UK, offering significant insights for the wider UK Higher Education sector. Using a qualitative design, data were collected through four focus groups. Thematic analysis identified three main themes and three subthemes. The main themes were: “wider factors impact the PhD,” “sense of community empowers the PGR journey,” and “the impact of support.” Subthemes included accommodation challenges, the importance of pastoral support, and employment for income and experience. The findings show that international PGR progression depends on far more than academic support, addressing a critical gap in understanding their settlement challenges. Given that most existing research primarily examines academic needs, this study makes an important contribution to the literature.